Vena saphena magna in situ arterializacija gebstint koją: atvejo aprašymas - Cvetanovski, Vlatko; Arsovski, Andreja; Stojanovska, Liljana; Cvetanovska, Marija; Dimitrov, Zoran (Lietuvos chirurgija, 2018)
[straipsnis ir santrauka anglų kalba]